A study of the role of guanxi for value-added supply chain innovation. Issue 1 (2nd January 2023) - Wang, Michael; Lee, Paul Tae-Woo; Chan, Ricky Y. K.
ABSTRACT: This paper aims to investigate the relationships between guanxi, supply chain innovation, and stakeholder's value in a value-added supply chain innovation model, taking the empirical data from New Zealand firms. Based on the resource-based view and stakeholder theory, it proposes a research model in which guanxi is an antecedent of supply chain innovation and stakeholder value. The value-added supply chain innovation model was established through the structural equation model (SEM), which was performed to validate the measurement models and test the research hypotheses. The empirical test results shed light on value-added supply chain innovation in association with guanxi . This knowledge can help to deliver more effective innovation outcomes and generate more effective value creation in supply chains, thus benefitting all stakeholders. The study contributes by providing both theoretical expansion and empirical evidence related to supply chain innovation and by establishing a value-added supply chain innovation model.